(untitled) (Филологические заметки, 2019)
The article deals with the term humanism and sketch problems of humanism in a technological society. It is argued that humanism represents an uncritical acceptance of boundaries between humans and non-human beings, making human being a center of moral concern in an elitist way of creating center and periphery of moral horizon. Humanism based on that ground seems to be a dominant one in determining the way humans deal with the environment. If an uncritically prioritized boundary is always placed around the human element, then that which is seen as lying beyond the human boundary (our “environment”) will inevitably be marginalized and misuse of “morally passive” elements in moral conduct thus finding its justification. There are some examples of attempts of humanizing non-human elements which is signify rising awareness of the need for crossing boundaries between “us” (human beings) and “them” (rest of the nature). That ambitious goal with clumsy method is seen as the sign of specific bioethical sensibility and it is argued in favor of a new conception of humanism empowered by bioethical approach to the problems of technological society.